Main Trends in Formative Assessment in Basic Education (Docentes 2.0 Journal, 2024)
Unlike summative assessment, formative assessment focuses on the learning process, continuously providing real-time feedback with appropriate adjustments to educational strategies. The research objective was to conduct an exhaustive bibliometric review on formative assessment in basic education, finding patterns, trends, and emerging areas in scientific production. Its development was based on the systematic method, positivist paradigm, and mixed approach, with a descriptive narrative design, bibliographic documentary type, and cross-sectional. Academic publications on formative assessment in basic education were analyzed from 2010 to 2024, and studies were selected using specific inclusion and exclusion criteria. Bibliometric analysis techniques and data analysis tools were used to collect information from each study. The instruments included data extraction tables that recorded titles, authors, year of publication, source, objectives, methodology, results, and conclusions. The analysis revealed an evolution in research production, with significant increases in certain periods. Discussions focused on challenges in implementing formative assessments, such as resistance to change and the need for adequate teacher training. Finally, the issue of integrating formative assessment into educational programs and providing the necessary support to teachers for effective implementation, thus improving the quality of basic education, was addressed.
Keywords: Formative assessment; basic education; feedback; academic performance